THE MOTIVATING FUNCTION OF MYTH: A COGNITIVE ONOMASIOLOGICAL ANALYSIS - Elena Sеlivanova; Valentyna Kalko; Nikolay Kalko (Езиков свят)
The article is devoted to the investigation of such special designation type of words and idioms: the mythological ones. This type is characterized by the choice of formative stems from such fragment of ethnic consciousness, which is unfoundedly taken on trust, that is a myth in the narrow meaning of this term; myth units not removing superstitions, popular belief, signs, etc. A myth is irrational, axiomatic, unfounded cognitive structure, which has powerful ability of transfer by next people generations, informative stability, absence of depth of sense, tendency of disappearance and production of new myths and others like that. Mythological motivation is appropriated to the signs of cultural codes of animals and plants; also, idioms and proverbs can have propositional, associative-metaphorical and value statuses. Mythological motivation nominative units can be of propositional, metaphorical, or evaluative character. Thus, proposition that lies in the basis of mythological motivated words and expressions, is non-controversial. It establishes an unverified idea. Sometimes mythological nominative units can be of metaphorical nature. It is explained by the fact that a myth accumulates figurative layers and hides behind the metaphorical designations of its eventual canvas. The essence of such mythological motivation words and phraseological units in using signs of one cultural code or concept for designating others. Mythologemes can reflect the evaluation of certain nominative units by ethnic consciousness their subdivision on useful and harmful, good-looking and ugly. Evaluation derives mostly from folk beliefs and Christian mythology. Mythological motivation nominative units make it possible to penetrate into the remote layers of folk consciousness and ascertain its reflections in the ethnic culture.